Capillary Active Interior Insulation Systems for Wall Retrofitting: A More Nuanced Story. Issue 5 (3rd July 2016) - Vereecken, Evy; Roels, Staf
ABSTRACT: To thermally upgrade exterior masonry walls, interior insulation is often the only possible retrofitting technique, especially when dealing with historic buildings. Unfortunately, it is also the riskiest post-insulation technique, as frost damage, interstitial condensation, and other damage patterns might be induced. To diminish those risks, nowadays so-called capillary active interior insulation systems are often promoted. These systems aim a minimal reduction of the inward drying potential, while interstitial condensation is buffered. Currently, several capillary active systems are on sale. These different types have, however, widely varying properties. In this article, a closer look at the hygrothermal properties and the working principle of a number of "capillary active" interior insulation systems is made. The spread in capillary absorption coefficients and the vapor diffusion resistances of the different systems is discussed and their influence is illustrated. Based on all this, a more nuanced view on capillary active insulation systems is pursued. Abbreviations: AC: aerated concrete; CaSi: calcium silicate; GM: glue mortar; GB: gypsum board; HAMFEM: Heat Air and Moisture Finite Element Method; MW: mineral wool; PE: polyethylene; PIR: polyisocyanurate; PUR: polyurethane; VIP: vacuum insulation panel; WFB: wood fiber board; XPS: extruded polystyrene; sddry : dry vapor diffusion resistance factor; µdry : dry vapor diffusion resistance